Exploring the Relationships Among AI, Agrifood Supply Chain Management Practices,Resilience, and Performance - Fengzhao, Yin; Lo, May Chiun; Abang Azlan, Mohamad; Sin, Kit Yeng (SHPMedia Sdn Bhd, 2025)
This study investigates the impact of artificial intelligence (AI) on agri-food supply chain resilience (ASCR) and performance in China's agricultural sector. Using data collected from 194 senior executives of Chinese agri-food companies during August-September 2024, the research examines how organizational factors-top management support (TMS), supplier integration (SI), internal management (IM), customer integration (CI), and supply chain collaboration (SCC)-influence ASCR, and how AI moderates these relationships. Employing partial least squares structural equation modeling (PLS-SEM), the findings reveal that TMS, IM, and CI significantly enhance ASCR, with AI demonstrating a significant moderating effect specifically on the IM-ASCR relationship. The study contributes to understanding how digital transformation through AI can enhance supply chain resilience and performance in the agri-food sector. These findings provide practical insights for agri-food executives in developing effective strategies to improve supply chain resilience and performance through AI integration, particularly in the context of emerging markets.